Implementasi Analytical Hierarchy Process Dalam Pemilihan Arduino Board - Kresna Ramanda; Susanto Susanto; Arief Rusman (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Internet Of Things (IoT) is one of the trends that is in demand to carry out various automation and control of devices or machines easily anytime and anywhere, the existing Internet Of Things (IoT) devices are of various kinds according to the needs of the One of the users is the Arduino Board. Arduino is a microcontroller board based on the ATmega328P microchip which is used to control various electronic components. Analytical Hierarchy Process is applied in the selection of Arduino board in data calculation and analysis with the addition of Expert Choice software. Primary data collection is by suggesting the criteria used as variables in the assessment. Primary data is obtained from questionnaire data that has been filled in by each respondent. Giving weight of the assessment based on each respondent's data according to the criteria consisting of Cost, Clock Speed, Flash Memory, SRAM, Connectivity, and the number of input / output pins. The result of this study is that the connectivity criteria is the most important criterion for respondents for the Arduino Board assessment, which is 34.2%. For the priority order for the alternative Arduino board, the first is ESP32 of 25.6%, ESP12F of 20%, MCU v3 Node of 19.9%, WEMOS D1 mini of 18.9%, Mega rev3 of 9.9% and the last is uno R3 of 5.7%.